2020
DOI: 10.3390/su12041490
|View full text |Cite
|
Sign up to set email alerts
|

What Could China Give to and Take from Other Countries in Terms of the Development of the Biogas Industry?

Abstract: Anaerobic digestion is one of the most sustainable and promising technologies for the management of organic residues. China plays an important role in the world's biogas industry and has accumulated rich and valuable experience, both positive and negative. The country has established relatively complete laws, policies and a subsidy system; its world-renowned standard system guarantees the implementation of biogas projects. Its prefabricated biogas industry has been developed, and several biogas-linked agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…The development of biogas production corresponds to that program. China has developed many types of household biogas digesters since the 1980s to overcome the weaknesses of traditional brick and concrete digesters (Lei et al 2020). Among all the traditional digesters, the Chinese dome digester is the most popular one due to its reliability.…”
Section: General Results About China and Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The development of biogas production corresponds to that program. China has developed many types of household biogas digesters since the 1980s to overcome the weaknesses of traditional brick and concrete digesters (Lei et al 2020). Among all the traditional digesters, the Chinese dome digester is the most popular one due to its reliability.…”
Section: General Results About China and Africamentioning
confidence: 99%
“…It has become a standard for the design of domestic prefabricated digesters like the Puxin digester (Jegede et al 2019). The most common prefabricated biogas digesters in China are flexible plastic digesters and composite material digesters (Lei et al 2020). Flexible plastic digesters are very efficient due to their low cost and ease of implementation and use.…”
Section: General Results About China and Africamentioning
confidence: 99%
“…FIT schemes for gas supply should be institutionalized in Japan. Zheng et al (2020) showed the importance of subsidizing the production of BGPs [57]. It may be possible to consider support in the form of environmental, social, and governance (ESG) investments from the viewpoint of improving environmental problems and regional economies, for which the dairy farmers who are willing to adopt BGPs would be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Germany published the detailed guideline on the safe use of material for the construction of biogas technology 85 . Comparing biogas technology in well‐developed countries in Europe, household biogas digester is specific because of their application in the intensive farm for power generation in Europe 86 . In term of biogas engineering standard, China dominated the biogas standard and the number accounts for approximately 1/3 of the total biogas standard 82 .…”
Section: Biogas Standard Systemmentioning
confidence: 99%
“…85 Comparing biogas technology in well-developed countries in Europe, household biogas digester is specific because of their application in the intensive farm for power generation in Europe. 86 In term of biogas engineering standard, China dominated the biogas standard and the number accounts for approximately 1/3 of the total biogas standard. 82 Wang et al 17 reported that biogas standard system in other developing countries is difficult to match with the Chinese biogas standard pace.…”
Section: Cost Of Materials Used For the Construction Of Biogas Digementioning
confidence: 99%